A Comparative Performance Evaluation of LIC and Private Players with Regard to Death Claims: A Comparative Analysis of Death Claims in the Life Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Life Insurance in its modern form came to India from England in the year 1818. Oriental Life Insurance Company started by Europeans in Calcutta was the first Life Insurance company on Indian Soil. The first two decades of the twentieth century saw lot of growth in Insurance business. On December 7, 1999, Parliament passed the Insurance Regulatory and Development Authority (IRDA) Act which paved the way for granting licences to private sector life-insurance companies. Life Insurance is the fastest growing sector in India since 2000 as Govt. allowed private players and FDI upto 26. Therefore, monopoly of LIC came to an end and the corporation has to perform in a competitive environment. In the present paper, an attempt has been made to analyse the growth of insurance sector with regard to individual death claims and group death claims. A comparative study has been done regarding the death claims of LIC and various other private players.